Narrativas (auto)biográficas, processos de aprendizagem da docência e desenvolvimento profissional de professores que ensinam Matemática: contribuições para o campo da educação matemática - Lagoeiro, Fabio Gomes (Universidade Federal de São Carlos, 2021)
The (auto)biographical research in the field of Education associated with the process of teacher education and professional development have been increasingly consolidated in the scientific field. Regarding the link between Mathematics Education and (Auto)biographical Research, it is worth noting that studies guided by the (auto)biographical method have stood out on the national scene, especially in the field of research concerning the teacher who teaches Mathematics (PEM), focus of this study. In this sense, the investigation carried out, of a qualitative nature, aims to investigate aspects related to the teaching learning processes and professional development evidenced by the (auto)biographical narratives of teachers who teach Mathematics. From this objective, we sought to highlight the heuristic and formative role of (auto)biographical sources as material for the study of the trajectories of teacher education who teach Mathematics, exploring the epistemological and methodological principles of (auto)biographical narratives that enhance references and listening to oneself, the lessons learned and the implications of the training trajectories of teachers who teach Mathematics. To answer the central question – which contributions regarding the teaching learning processes and professional development of PEM emerge from (auto)biographical research for the field of Mathematics Education? – a corpus was created with scientific productions related to Mathematics Education and (Auto)biographical Research in the dialogue with the PEM, published in the Brazilian Digital Library of Theses and Dissertations (BDTD), considering the period from 1991 to 2021. In this movement, the analysis of the findings evidenced fundamental contributions of (auto)biographical research to the field of Mathematics Education, with regard to studies focused on the PEM. By highlighting trends and gaps in the production of knowledge, subsidies and paths for new studies are presented, in order to broaden perspectives and meet the demands that arise in the scientific field. It was possible to observe that the (auto)biographical approach has contributed, in the context of Mathematics Education, to the consolidation, conceptualization and characterization of the PEM as an expanding field of research.
(Auto)biographic narratives, teaching learning processes and professional development of teachers who teach Mathematics: contributions to the field of mathematics education
Keywords: Pesquisa (auto)biográfica; Aprendizagem e desenvolvimento profissional docente; Educação Matemática; Narrativas (auto)biográficas; Professores que ensinam Matemática; (Auto)biographical research; Learning and teacher professional development; Mathematics Education; (Auto)biographical narratives; Teachers who teach Mathematics; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO